Fatigue Life Prediction Model of Cylindrical Gears Based on the Energy Accumulation Curve - Liu Shicong; Yang Jianwei; Li Xin; Gao Xiang (Jixie chuandong)
It is of great significance to establish a cylindrical gear bending fatigue life prediction model with a wide range of applications and easy calculation. Through the gear bending fatigue test combined with the simulation results of the finite element model, the energy accumulation curve at the root of the tooth under different stress amplitudes is calculated. On the basis of the energy accumulation curve, the fracture cumulative energy curve under different stress amplitudes is obtained, and a cylindrical gear bending fatigue life prediction model is proposed based on the Palmgren-Miner linear cumulative damage theory and the above curve. Combined with the test results of gear bending fatigue tests under different stress amplitudes, the test results are all within the ± 3 life factor scatter bands, which proves that the model can accurately predict the gear bending fatigue life.